The Influence of Metabolic Factors for Nonalcoholic Fatty Liver Disease in Women - Goh Eun Chung (BioMed Research International, 2015)
Background/Aims. Women after menopause have increased insulin resistance and visceral fat, which may increase the prevalence of nonalcoholic fatty liver disease (NAFLD). However, the pathogenesis of NAFLD in women has not been clearly defined. In this study, we aimed to determine the risk factors for NAFLD in women. Methods. A retrospective cohort study was conducted. Women who underwent abdominal ultrasonography and blood sampling for routine health check-ups were recruited. Results. Among 1,423 subjects, 695 women (48.9%) were in a menopausal state. The prevalence of NAFLD was higher in postmenopausal women than in premenopausal women (27.2% versus 14.4%, P<0.001). In premenopausal women, low HDL-cholesterol, central obesity, and homeostasis model assessment-estimated insulin resistance showed a significant association with the increased risk of NAFLD in multivariate analysis. In postmenopausal women, the presence of diabetes, triglyceridemia, and central obesity showed a significant association with the risk of NAFLD. The presence of menopause and hormone replacement therapy in postmenopausal women were not risk factors for NAFLD. Conclusions. Our findings showed different metabolic factors for NAFLD in pre- and postmenopausal women. However, the key issues are the same: central obesity and insulin resistance. These results reemphasize the importance of metabolic factors irrespective of menopausal status in the pathogenesis of NAFLD in women.